2002
DOI: 10.2355/isijinternational.42.974
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Analysis and Numerical Simulation of High Frequency Electromagnetic Field in Soft Contact Continuous Casting Mold.

Abstract: The electromagnetic parameters in soft contact continuous casting billet mold were analyzed in this paper by mathematical analytic method and numerical simulation; the optimized frequency range was fixed on 20 000-40 000 Hz. The distribution of magnetic flux density and electromagnetic body force in split mold was obtained; the research results achieved respectively by mathematical analytic method and numerical simulation agree with each other. With increase of frequency of electromagnetic field, the electroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…In view of the rationality of the divisional elements, the width of the gap between the strand and the mold wall was set as 1 mm. Basic assumptions 11) : 1) The liquid metal level was supposed to be plane, and the effect of the meniscus shape on magnetic field was neglected. 2) The liquid metal level was located at the middle of the coil.…”
Section: Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of the rationality of the divisional elements, the width of the gap between the strand and the mold wall was set as 1 mm. Basic assumptions 11) : 1) The liquid metal level was supposed to be plane, and the effect of the meniscus shape on magnetic field was neglected. 2) The liquid metal level was located at the middle of the coil.…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…Many researchers carried out long-term studies on the distribution of the electromagnetic field in the soft-contact solidification process and obtained many important results. [11][12][13] But up to now, the researches on the distribution of electromagnetic field have mostly concentrated on the case of the slit mold for SC-EMCC. Investigations on slitless mold for SC-EMCC are very lacking, except for the literatures 8,9) that have introduced the structure of the two-section slitless mold, further research has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…This results in increasing the Joule heat, exhibited by the increase of mould wall temperature. The enhancement of the mould temperature due to Joule heat can also be found in the numerical simulation work of Na et al [24,25].…”
Section: Alloy Pool Temperature Variation With Pmentioning
confidence: 64%
“…[1][2][3][4][5][6][7][8][9][10] For example, the thermal-driven buoyancy flow (also called natural convection, thermal convection or non-isothermal flow in some papers) in tundish and ladle with large volume capacity of liquid steel has been widely studied. [11][12][13][14] It is thought that non-isothermal flow has an obvious influence on the temperature distribution and inclusion removal in tundish and ladle.…”
Section: Introductionmentioning
confidence: 99%